The Inter-Relationship of Periostin, TGFβ, and BMP in Heart Valve Development and Valvular Heart Diseases. (2011) - Conway, Simon J.; Doetschman, Thomas; Azhar, Mohamad
Abstract : Recent studies have suggested an important role for periostin and transforming growth factor beta (TGFβ) and bone morphogenetic protein (BMP) ligands in heart valve formation and valvular heart diseases. The function of these molecules in cardiovascular development has previously been individually reviewed, but their association has not been thoroughly examined. Here, we summarize the current understanding of the association between periostin and TGFβ and BMP ligands, and discuss the implications of this association in the context of the role of these molecules in heart valve development and valvular homeostasis. Information about hierarchal connections between periostin and TGFβ and BMP ligands in valvulogenesis will increase our understanding of the pathogenesis, progression, and medical treatment of human valve diseases.